FROM OVERPROTECTION TO INDEPENDENCE: INVESTIGATING THE RELATIONSHIP BETWEEN HELICOPTER PARENTING, PEER ATTACHMENT, AND EMOTIONAL MATURITY IN UNIVERSITY STUDENTS (Contemporary Journal of Social Science Review, 2025)
Background and Aim: In recent years, the phenomenon of helicopter parenting characterized by overinvolvement and excessive control in children's lives has raised concerns about its impact on young adults’ social and emotional development. The aim of the present study was to investigate the relationship between helicopter parenting, peer attachment and emotional maturity in university students.Methodology: A correlation research design and non-probability convenience sampling technique was used to collect data (N=300) consisted 144 females with 48% and 156 males with 52% recruited from Government and Private Universities of Lahore by using self-report measures. The sample was consisted of both male and female with age range 18-25 years. The results of the study were analysed through SPSS-21. Results: Results revealed that helicopter parenting was positively correlated with autonomy support, while peer attachment especially trust and communication was positively linked to emotional maturity. Peer alienation showed negative associations. Stepwise regression indicated that peer trust and alienation significantly predicted emotional maturity. Notably, autonomy support had a negative predictive value. Additionally, male students reported higher emotional maturity than females.Conclusion: The study concludes that peer relationships, particularly trust and reduced alienation, play a critical role in fostering emotional maturity among university students, while the impact of helicopter parenting and autonomy support is more complex and culturally influenced.